ChemInform Abstract: Organocatalyzed Multicomponent Synthesis of Isoxazolidin‐5‐ones. Issue 12 (March 2016) - Berini, Christophe; Sebban, Muriel; Oulyadi, Hassan; Sanselme, Morgane; Levacher, Vincent; Briere, Jean‐Francois
Abstract: DABCO‐catalyzed three‐component reaction of Meldrum′s acid, N‐protected hydroxylamines and alkyl or aryl aldehydes gives the title compounds in good to high yields.